The Effectiveness of Group Therapy on the Family Functioning of Individuals under Methadone Treatment: A Clinical Trial - Hassan Ziaaddini; Batoul Ebrahim Nejad; Nouzar Nakhaee (Addiction and Health, 2013)
Background: A significant number of opioid-dependent patients in Iran are now being treated by methadone maintenance therapy (MMT). One of the social complications of substance dependency is family disorganization and a decrease in marital satisfaction. This study aimed to determine the effect of group therapy based on the transtheoretical model of change on family functioning of the patients under MMT. Methods: In this open clinical trial, 48 married people who were between the ages of 19 and 40, and under methadone maintenance therapy had been assigned to two random groups of test and control. In the intervention group, group therapy was held based on the transtheoretical model of behavior change, for 29 sessions (two times a week). To assess the overall health and pathology of the family, the two questionnaires Family Assessment Device (FAD) and Marital Conflict Questionnaire (MCQ), both with approved reliability and validity, were used. Findings: A total of 24 patients in the control group and 23 patients in the intervention group (one person withdrew from the study in the early meetings) were evaluated. The mean ± SD of age of the control and intervention groups, respectively, were 33.9 ± 4.8 and 32.8 ± 4.3 (P = 0.40). Before the intervention began the average score of FAD and MCQ questionnaires between the two groups was comparable. After the intervention was over the score of each of the two questionnaires, with the adjustment of the baseline score, was lower in the treatment group than the control group, the difference was marginally significant (P < 0.10). Conclusion: The family functioning of the MMT treated patients showed improvement. Therefore, with the use of stage-of-change and group therapy, steps can be taken for improving family functioning of these patients. Due to the relatively long duration and frequency of treatment sessions the feasibility of this intervention needs further research. Keywords: Behavior change, Marital satisfaction, Drug dependence, Transtheoretical model